Geological and hydrometeorological hazards affecting livestock production in Ethiopia: a systematic review of impacts, mitigation, and adaptation strategies - Teku, Degfie; Derbib, Tarekege (Frontiers in Earth Science, 2025)
IntroductionEthiopia’s livestock sector is critically vulnerable to a wide range of geological and hydrometeorological hazards that undermine animal health, productivity, and the livelihoods of pastoral communities. The country’s geographic location along the East African Rift System increases its susceptibility to geological threats such as volcanic eruptions, earthquakes, and landslides, while climate variability exacerbates hydrometeorological risks including droughts and floods.MethodsThis systematic review adheres to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and employs a structured search strategy across major academic databases including Scopus, Web of Science, and Google Scholar. Studies were selected based on predefined inclusion and exclusion criteria to ensure the relevance and quality of the literature reviewed.ResultsThe review synthesizes findings from high-quality studies to qualitatively assess the compound impacts of geological and hydrometeorological hazards on livestock production in Ethiopia, particularly within pastoral and agro-pastoral systems. Drought emerges as the most significant hazard, with more than 6.8 million livestock deaths reported since 2020 due to successive failed rainy seasons. Floods have also caused severe damage; for instance, the 2006 flooding in the Southern Nations, Nationalities, and Peoples’ Region (SNNPR) resulted in the loss of approximately 15,600 livestock. In contrast, direct data on geological hazards such as volcanic eruptions and earthquakes remain limited, though their indirect effects—such as ashfall on grazing lands, water contamination, and disruption of grazing routes—further compromise livestock productivity and resilience.DiscussionThe review highlights critical gaps in data and research, particularly regarding the direct impacts of geological hazards. It identifies key adaptation and mitigation strategies, including early warning systems, hazard mapping, veterinary service enhancement, livestock diversification, and the promotion of livestock insurance schemes. Strengthening policy frameworks, community engagement, and economic instruments is essential to build resilience in the livestock sector. Evidence-based interventions are urgently needed to safeguard livelihoods, ensure food security, and promote sustainable adaptation in Ethiopia’s hazard-prone regions.